Wykluczenie prawa do potomstwa (kan. 1101 § 2 KPK) w świetle wyroku Roty Rzymskiej c. Sciacca z 27 kwietnia 2007 r. - Urbanowska-Wójcińska, Dorota (Ius Matrimoniale, 2016)
The judgment (pro nullitate matrimonii) was issued in the third instance (it was negative in the first instance and positive in the second instance) due to the exclusion bonum prolis (can. 1101 § 1 CIC) by the man. On the basis of testimonies of the petitioner and witnesses, after taking into consideration all circumstances, especially cause of simulation which was pessimistic view of the world and all entire life, Roman Rota judges had no doubt that the petitioner excluded the good of offspring by his positive act of will.